You are on page 1of 8

1

1.1
-

1. ;

2. , ,
;

3. i) ;
ii) ;

4. i) ;
ii) ;

5. ;
- -
1

6. :
x2 + 5 |x| 4
i) f (x) = ii) f (x) = 2
2x 6 x +x6
x 2x 9
iii) f (x) = 3 iv) f (x) =
x 4x 7x + 10
2 |x 3| 5

7. :
i) f (x) = x 3 ii) g(x) = x2 + 3x 4
x
iii) h(x) = iv) K(x) = ln(2 x2 )
4 x2
8. :
1 x2 x
i) f (x) = ii) g(x) = ln(x 2) +
x x5
iii) h(x) = 2x 1 + ln(5 x)

9. ,
x x y y.
|x| 2
i) f (x) = x2 6x 7 ii) f (x) = 2
x +1
x2 1
iii) f (x) = iv) f (x) = ln(x 2)
x

1
2 1.

x 5
10. f (x) = R,
x1
A(4, 7).

i) f .
ii) .
iii) x x
y y.

11. x f (x) = 2x2 x 6


x x;
x2 1
12. f (x) = .
|x| 1
i) f .
ii) .
iii) x
y = 5;

13. f (x) = x2 1 A(x, y)


f.

) x.
) d(x) x
d(x).
)
1.

14. ,
20m. x m, :

) x.
) E(x) ,
.
) E(x) 25m2 .
)
, ;
{
x+2
x < 1
15. f (x) = x12
2x x + x 1

i) f (0), f (2) f (1).


ii) f (1) = f (2) 2f (0) .

16. f (x) = x2 x + 1 g(x) = x2 + x.


:
f
i) f + g ii) f g iii) f g iv) g
2
x2 + x +
17. f (x) = .
x2

y y A(0, 1) B(3, 2).

i) f .
1.1. 3

ii) .
iii) .
iv) .

18. f (x) = 2x2 + x + , R.


A(1, 7) B(2, 4) :

i) .
ii) f x x y y.
1 x+4
19. f (x) = g(x) = .
x2 16 x4
:
f
i) f + g ii) f g iii) f g iv) g
4 1.

1.2 -
-

1.
.

() f, g lim f (x) = l1 lim g(x) = l2 , l1 , l2


xx0 xx0
, lim (f (x)g(x)) = l1 l2
xx0
() lim x = x0 .
xx0
() lim x = x0 .
xx0

2. f A;
- -
1

3. :
x2 + 5x x2 9
i) lim ii) lim
x2 3x + 8 x3 2x 6
5x 5 x2 4x 12
iii) lim 2 iv) lim
x1 x 1 x2 5x + 10
4. :
6x2 11x + 5 x3 5x + 2
i) lim ii) lim
x1 x2 + x 2 x2 x2 4

5.
:
x1 x+12
i) lim ii) lim
x1 x 1 x3 4x 12
x2 1
iii) lim
x1 3 8 x

x 2
iv) lim 2
x2 2x 3x 2
{ 2
x +4x5
x3 1
x < 1
6. f (x) = . lim f (x)
x + 3x 2 x 1
5 4 x1

{ 2
x +5x14
x3 1
x = 2
7. f (x) = .
2 x = 2
x0 = 2.
{ 3
x 27
x3 x = 3
8. f (x) = .
7 x = 2
x0 = 3.
{ 2
3x +14x5
x = 5
9. f (x) = x+5 , R.
x = 5
x0 = 5.
{ 2
7x 18x+8
x = 2
10. f (x) = 2x4 , R.
6 + 14 x = 2
2

x0 = 2.
1.2. - 5
{
x2 9
x < 3
x+3
11. f (x) = .
5x x 3
x2 +
R.
2
{
4x + 1 x < 1
12. f (x) = , R.
ln x + x + 5 x 1
2

R.


x + 3x 5 + 1 x < 2
2

13. f (x) = 4 x = 2 , , R.

x2 +3x+2
x2 + x + x 2
, R.
6 1.

1.3 -
-

1. x0 ;

2. .

() f x0 y = f (x) x,
x = x0 .
()
f (x0 , f (x0 )) f (x0 ).
()
x = f (t), t0 , (t0 ) = f (t0 ).

3.
.

4. f ;

5. f (x) = c. f (x) = 0.

6. f (x) = x. f (x) = 1.

7. f (x) = x2 . f (x) = 2x.

8. f (x) F (x) = cf (x). F (x) = cf (x).

9. f (x) g(x) F (x) = f (x) + g(x).


F (x) = f (x) + g (x).

10. :

(c) = ...... (cf (x)) = ......


(x) = ...... (f (x) + g(x)) = ............
(x ) = ...... (f (x)g(x)) = .....................
( )
f (x)
( x) = ...... = .........................
g(x)
(x) = ...... (f (g(x))) = ...............
(x) = ......
(ex ) = ......
(ln x) = ......

- -
1

11. :
i) f (x) = x3 6x2 + x + ii) f (t) = t2 + t + 1
iii) f (x) = x 5 x + ( + 1)x + 2
8 2 3

12. :
5 x1 ex 1
i) f (x) = x + ii) f (x) = x2 ex iii) f (x) = iv) f (x) =
x ex ex + 1
13. :
i) f (x) = x2 e1x ii) f (x) = ln(x2 2x + 3) iii) f (x) = (x2 x + 1)3
iv) f (x) = ex iv) f (x) = ex
1.3. - 7

14. f (x) = x x , , R. : f (x) + f (x) = 0


x
15. f (x) = .
x+1
i) .
ii) .
iii) f (0).

16. f (x) = ln(x2 + 1).

i) .
ii) .
iii) , f () = 1.

17. f (x) = e3x (x + x , x R. :

f (x) + 6f (x) + 10f (x) = 0

18. xm 2m .
x = 5m.

19. A(x, 0) , x > 0 B(0, x + 7).


:

) A B,
OAB.
) x = 5
x = 2, 5.

20. (t) cm
(t) = 2t + 1.
t = 4s.

21. f (x) = xex1


1.
2
x
22. f (x) = .
x2 + 1
f O(0, 0), xx.

23. f (x) = 3x2 11x + 8.


f xx 45.

24. f (x) = x3 3x2 + x + 1. f


y = 12x.

25. f (x) = ln(x + 1)2x + 3.


f x + y + 1 = 0.

26. f (x) = x2 + 5x2. f


x + 3y = 6.
8 1.

1.4
-

1. f ,
, .

2. .

() f f (x0 ) = 0 x0 (, ) , f (x) > 0 (, x0 )


f (x) < 0 (x0 , ), f (, ) x = x0 .
() f f (x) < 0
, f .

- -
1

3. , ,
:
i) f (x) = x2 8x + 3 ii) f (x) = x3 + 3x2 9x + 2

4. , ,
:
i) f (x) = xex ii) f (x) = x4 2x2 + 2

1 x
5. i) f (x) = 2 ii) f (x) =
x +1 x+1
6. , ,
:
ex
i) f (x) = 2x + x ii) f (x) = ln x x iii) f (x) =
x
2
1
7. f f (x) = x > 0. M (x, y)
x2
+1
f xx yy,
Ox, Oy .
M , .

8. 840
, 8 . 20
, 30 . x
20 , :

) , x, ,
.
) x .
) , x
;